(untitled) (Aintelia Science Notes, 2026)
Skin aging is characterized by moisture loss, a decrease in collagen, and a slowing of cellular renewal. During this process, structural and functional changes occur in the epidermis, dermis, and hypodermis layers. In this study, a multifunctional active complex containing hyaluronic acid, niacinamide, and hydrolyzed collagen was developed and incorporated into a facial serum at a 5% concentration. The formulation’s efficacy was evaluated over a 4-week period on 20 female volunteers aged 25–39. Following the application of the serum twice daily, an increase in skin hydration and smoothness, as well as a reduction in dryness and the appearance of fine lines, was observed. The findings indicate that the developed active complex provides skin brightening and is effective in reducing signs of aging.